Mechanistic Insights Into Probiotic Properties of Lactic Acid Bacteria Associated With Ethnic Fermented Dairy Products - Ghosh, Tamoghna; Beniwal, Arun; Semwal, Anupama; Navani, Naveen Kumar (Frontiers in Microbiology, 2019)
Gut microbes and their metabolites maintain the health and homeostasis of the host by communicating with the host via various biochemical and physical factors. Changing lifestyle, chronic intake of foods rich in refined carbohydrates and fats have caused intestinal dysbiosis and other lifestyle-based diseases. Thus, supplementation with probiotics has gained popularity as biotherapies for improving gut health and treating disorders. Research shows that probiotic organisms enhance gastrointestinal health, immunomodulation, generation of essential micronutrients, and prevention of cancer. Ethnically fermented milk and dairy products are hotspots for novel probiotic organisms and bioactive compounds. These ethnic fermented foods have been traditionally prepared by indigenous populations, and have preserved unique microflora for ages. To apply these unique microflora for amelioration of human health, it is important that probiotic properties of the bacterial species are well studied. Majority of the published research and reviews focus on the probiotic organisms and their properties, fermented food products, isolation techniques, and animal studies with their health pathologies. As a consequence, there is a dearth of information about the underlying molecular mechanism behind probiotics associated with ethnically prepared dairy foods. This review is targeted at stimulating research on understanding these mechanisms of bacterial species and beneficial attributes of ethnically fermented dairy products.